Robust approximations to the distribution of link distances in a wireless network occupying a rectangular region. - Mullen, John P. (Mobile computing and communications review.)
An important characteristic of a Mobile Ad Hoc Network (MANET) is the distribution of the link distance between communicating nodes. Knowing this distribution is a step in determining the distribution of the number of neighbor nodes, the number of hops required to transmit a message, etc. This paper presents two robust approximations to the link distance distribution for nodes within a rectangular area, providing the x and p node coordinates follow independent continuous spatial distributions. This paper also presents an approximate link distance distribution for the Random Waypoint Mobility model and examines the approximation error in a number of situations.